Efficient complement-mediated lysis of cells containing the CAMPATH-1 (CDw52) antigen. - Xia, M; Hale, G; Waldmann, H (1993)
CAMPATH-1 antibodies recognise a unique molecule on human lymphocytes and are unusually efficient at causing cell lysis with homologous complement. They have been successfully used for lymphocyte depletion in vivo in a variety of diseases. The antigen is a small glycosylphosphatidylinositol (GPI)-anchored glycoprotein with a mature peptide comprising only 12 amino acids and one N-linked glycosylation site at Asn3. The antigenic epitope is found in a proteolytic fragment containing the C-terminal tripeptide and the GPI anchor. Both the native and deglycosylated antigen as well as the proteolytic fragment can be reincorporated into various target cells, conferring sensitivity to lysis by CAMPATH-1 antibodies. These results imply that the special feature of the antigen which makes it a good target does not reside in the N-linked sugar or the first nine amino acids: instead they support the hypothesis that the proximity of the antigenic epitope to the cell membrane is more important.